2018
DOI: 10.1002/cmdc.201800463
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Positive and Gram‐Negative Antibiotic Activity of Asymmetric and Monomeric Robenidine Analogues

Abstract: Desymmetrisation of robenidine (1: N′,2‐bis((E)‐4‐chlorobenzylidene)hydrazine‐1‐carboximidhydrazide) and the introduction of imine alkyl substituents gave good antibiotic activity. Of note was the increased potency of two analogues against vancomycin‐resistant Enterococci (VRE), one of which returned a MIC of 0.5 μg mL−1. Five analogues were found to be equipotent or more potent than the lead 1. Introduction of an indole moiety resulted in the most active robenidine analogue against methicillin‐resistant S. au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
2
12
0
Order By: Relevance
“…mp 206–207 °C (amorphous solid). 1 H NMR (DMSO- d 6 , 400 MHz): δ 10.6 (s, 2H), 7.98–8.13 (m, 3H), 7.54 (s, 2H), 7.47 (d, 2H, J = 4.0 Hz), 7.23–7.27 (m, 2H), 7.14 (d, 2H, J = 4.0 Hz), 2.33 (s, 6H) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…mp 206–207 °C (amorphous solid). 1 H NMR (DMSO- d 6 , 400 MHz): δ 10.6 (s, 2H), 7.98–8.13 (m, 3H), 7.54 (s, 2H), 7.47 (d, 2H, J = 4.0 Hz), 7.23–7.27 (m, 2H), 7.14 (d, 2H, J = 4.0 Hz), 2.33 (s, 6H) …”
Section: Methodsmentioning
confidence: 99%
“…mp 229–230 °C (amorphous solid). 1 H NMR (DMSO- d 6 , 400 MHz): δ 10.64 (s, 2H), 8.46 (s, 2H), 7.94 (d, 2H, J = 2 Hz), 7.21–7.29 (m, 6H), 2.41 (s, 6H) …”
Section: Methodsmentioning
confidence: 99%
“…The indole dimer 20 (MIC: 1.0 and 4.0 µg/ml) showed potential activity against MRSA and VRE, and the SAR indicated that the indole moiety was crucial for the activity, and replacement of the indole skeleton by phenyl or pyridinyl was detrimental to activity. [ 47 ] The naphthalene‐containing indole dimers 21 (MIC: 5.0–522 µg/ml) and 22 (MIC: 11–193 µg/ml) were sensitive to S. aureus and MRSA, and the most active dimer 21a (MIC: 5.0 µg/ml) was comparable to linezolid (MIC: 6.0 µg/ml) and vancomycin (MIC: 3.0 µg/ml) against the two strains, and it was 9.6‐fold more potent than oxacillin (MIC: 48 µg/ml) against MRSA. [ 48 ] In addition, this dimer was nontoxic toward human HEK and SH‐SY5Y cells.…”
Section: Indole Dimersmentioning
confidence: 99%
“…As part of a series of studies we have developed a number of classes of biologically active molecules [ 15 , 16 , 17 , 18 , 19 , 20 ]. With our in-house compound library, we sought to examine one of our compound series, that were originally designed to target the aryl hydrocarbon receptor (AhR) ( Figure 1 ) [ 15 , 21 , 22 , 23 ], for activity against methicillin-resistant Staphylococcus aureus (MRSA), E. coli , Klebsiella pneumoniae , Acinetobacter baumannii and Pseudomonas aeruginosa ; and the yeasts Candida albicans and Cryptococcus neoformans .…”
Section: Introductionmentioning
confidence: 99%